ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN MENUNAIKAN ZAKAT PROFESI (STUDI KASUS PADA GENERASI MILENIAL KOTA TANGERANG) - Tabhina, Rafa Kayla; Ekawaty, Marlina (Islamic Economics and finance in Focus, 2022)
Indonesia is a country with a majority Muslim population and still experiencing poverty. One of the efforts to eradicate poverty in Islam is through zakat, especially professional zakat, which has considerable potential because it can be paid monthly or annually. The millennial generation is also said to be able to help optimize the zakat collection in Indonesia. Tangerang City is one of the regions in Indonesia called the City of Akhlakul Karimah. Hence zakat is the right step to eradicate poverty, especially from professional zakat, because Tangerang City is dominated by the millennial generation and has a fairly high Regional Minimum Wage (UMR) level. Therefore, this study aims to analyze the effect of zakat knowledge, social environment, and income on the decision to pay professional zakat for the millennial generation of Tangerang City. The approach used in this study is a quantitative approach through logistic regression analysis. The results showed that the social environment variable significantly affected the decisions of the millennial generation in Tangerang City in paying professional zakat. In contrast, there is no significant effect of the variable knowledge of zakat and income on the decisions of the millennial generation in Tangerang City in paying professional zakat.